2003
DOI: 10.1046/j.1095-8312.2003.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Webs of theridiid spiders: construction, structure and evolution

Abstract: Understanding the web construction behaviour of theridiid (comb-footed) spiders is fundamental to formulating specific evolutionary hypotheses and predictions regarding the reduction of orb-webs. We describe for the first time in detail the web construction behaviour of Achaearanea tepidariorum , Latrodectus geometricus , Theridion sisyphium and T. varians as well as webs of a range of other theridiids. In our survey we distinguish four major web types. Among webs with gumfooted lines, we distinguish between w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 28 publications
(39 reference statements)
2
106
0
2
Order By: Relevance
“…10B). Hadrotarsines are wandering ant specialists, so they do not build a prey-catching web (Benjamin & Zschokke 2003). As a general attribute, theridiids (e.g., Latrodectus and Steatoda) build irregular webs, which may be considered the ancestral web-building pattern (state 0).…”
Section: Introductionmentioning
confidence: 99%
“…10B). Hadrotarsines are wandering ant specialists, so they do not build a prey-catching web (Benjamin & Zschokke 2003). As a general attribute, theridiids (e.g., Latrodectus and Steatoda) build irregular webs, which may be considered the ancestral web-building pattern (state 0).…”
Section: Introductionmentioning
confidence: 99%
“…Mimetidae) [20]. These 'derived' araneoid webs are so highly transformed from the ancestral orbicular architecture that in the few cases in which the spider building behaviours have been studied [21][22][23], the stereotypical behavioural algorithms involved in orb web construction [9] are no longer identifiable as such. Furthermore, web architecture across Araneoidea is extraordinarily diverse, although still largely undocumented for the majority of species [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Benjamin and Zschokke (2003) have found in their research of webs built by this species that the webs remained in place for extended periods and were expanded and repaired, but no regular patterns of replacement were observed. Our study confirmed these findings.…”
Section: Discussionmentioning
confidence: 92%